Feedback control problems : using MATLAB and the control system toolbox. - Frederick, Dean K.; Chow, Joe H. (Boston, MA : PWS, 1995)
The book contains examples and a variety of problems related to the analysis and design of feedback control systems that can be solved with MATLAB and the Control System Toolbox.
Keywords: Matlab; Feedback control systems; Feedback control systems; MATLAB